Czy internet jest szansą na powrót do demokracji bezpośredniej? - Galewski, Tomasz (Is Internet a Chance of Getting Back to Direct Democracy?, 2005)
The article shows changes, that can appear in the political field as a result of Internets development. The author tries to answer the question: „Is it possible to get back to direct democracy?". The first part of the publication contains general characteristics of democracy as a form of exercising authority. There are also mentioned main disadvantages of direct democracy, such as: domination of majority, bureaucracy, possibility of manipulating electors by sociology and lack of responsibility by politician's decisions. In the further part the author describes the role of Internet in getting back to direct democracy. He presents the point of e-democracy which applies computer science in the political area. He also indicates some problems connected with implementation of direct democracy in the nowadays world, such as data security during elections by Internet or aversion of some part of society to modern technologies. In the last part of the article the author judges the chance of implementing e-democracy today and indicates tasks that should be done to make this process possible.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonomia i Międzynarodowe Stosunki Gospodarcze (11); 2005; nr 1077, s. 154-175